VAD Chemotherapy versus Bortezomib Containing Regimens as Remission Induction For ASCT in Multiple Myeloma: A Single Center Experience - Yıkılmaz, Aysun Şentürk (Int J Hematol Oncol Stem Cell Res, 2020)
Background: Complete response (CR) and very good partial response (VGPR) are targeted with pre-ASCT induction regimens in patients by diagnosed multiple myeloma (MM), who are candidates for ASCT. In this study, it was aimed to compare the response and survival evaluations of cases who underwent induction treatment by vincristine-doxorubicin-dexamethasone (VAD) protocol versus bortezomib containing regimens. Materials and Methods: The data of 96 ASCT eligible patients, retrospectively analyzed. P value> 0.05 was considered statistically significant. Results: While 66 cases had received bortezomib containing regimens as induction regimen, 30 cases had received VAD protocol. The total survival was 91.3 (st.s 6) months and 43 (st.s 7.9) months, respectively, when we compared the cases without ASCT and with ASCT (p = 0.001). The OS of patients who underwent ASCT after reaching at least VGPR was longer than the underwent ASCT without reaching VGPR (p=0.019). Post-ASCT PFS (p=0.717) and OS (p = 0.126) analyzes were performed in 74 cases undergoing ASCT treatment, there was no significant statistical difference when patients with treated by VAD protochol and treated by bortezomib containing regimens as pre-ASCT induction regimens was compared to each other. Conclusion: Whatever the type of induction regimen is, the level of response achieved before ASCT is important. The survival of the myeloma patients are much more influenced with HDT-ASCT as well as post-transplantation strategies to keep the patients in remission. Even though it is outdated, we think that the VAD protocol may be an option in patients who are not responding with the new generation of agents in the following days.